2012
DOI: 10.1126/science.1223269
|View full text |Cite
|
Sign up to set email alerts
|

Kepler-36: A Pair of Planets with Neighboring Orbits and Dissimilar Densities

Abstract: In the solar system, the planets' compositions vary with orbital distance, with rocky planets in close orbits and lower-density gas giants in wider orbits. The detection of close-in giant planets around other stars was the first clue that this pattern is not universal and that planets' orbits can change substantially after their formation. Here, we report another violation of the orbit-composition pattern: two planets orbiting the same star with orbital distances differing by only 10% and densities differing b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
313
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 385 publications
(331 citation statements)
references
References 85 publications
17
313
0
Order By: Relevance
“…Correcting for the lower equilibrium temperature of Kepler-87 c (T eq = 403.3), its envelope mass fraction is probably even higher than that. Planets such as Kepler-87 c, as well as the highly irradiated Kepler-11 and -36 systems Carter et al 2012), demonstrate that the great compositional variety that was found for gas giants also extends down to planets with intermediate masses between Earth and Uranus.…”
Section: Discussionmentioning
confidence: 99%
“…Correcting for the lower equilibrium temperature of Kepler-87 c (T eq = 403.3), its envelope mass fraction is probably even higher than that. Planets such as Kepler-87 c, as well as the highly irradiated Kepler-11 and -36 systems Carter et al 2012), demonstrate that the great compositional variety that was found for gas giants also extends down to planets with intermediate masses between Earth and Uranus.…”
Section: Discussionmentioning
confidence: 99%
“…On the very last day of working on this paper, the KOI 277 system with its two planets and their associated TTVs, was published by the Kepler team as confirmed and was designated Kepler-36 (Carter et al 2012). While our analysis is an independent discovery and confirmation of this system, Carter et al (2012) used a Newtonian model -this system is obviously nonKeplerian -and thus their analysis is more accurate.…”
Section: Koi 277 -An Exceptionally Strong Candidatementioning
confidence: 99%
“…While our analysis is an independent discovery and confirmation of this system, Carter et al (2012) used a Newtonian model -this system is obviously nonKeplerian -and thus their analysis is more accurate.…”
Section: Koi 277 -An Exceptionally Strong Candidatementioning
confidence: 99%
“…We therefore repeated the analysis after fixing the gravity of the models to this value. Such an approach is now routinely implemented in spectroscopic studies of seismic targets (e.g., Batalha et al 2011;Carter et al 2012;Thygesen et al 2012;Huber et al 2013) and is expected to provide more robust estimates of the physical parameters and ultimately chemical abundances. The temperature was also determined from Fe excitation balance.…”
Section: Determination Of Stellar Parametersmentioning
confidence: 99%